2012
DOI: 10.1016/j.bioorg.2011.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms and inhibition of uracil methylating enzymes

Abstract: Uracil methylation is essential for survival of organisms and passage of information from generation to generation with high fidelity. Two alternative uridyl methylation enzymes, flavin-dependent thymidylate synthase and folate/FAD-dependent RNA methyltransferase, have joined the long-known classical enzymes, thymidylate synthase and SAM-dependent RNA methyltransferase. These alternative enzymes differ significantly from their classical counterparts in structure, cofactor requirements and chemical mechanism. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
43
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 49 publications
2
43
0
Order By: Relevance
“…The remote folate binding site found here might represent crystallographic trapping (of no functional implications). Alternatively, it could indicate an allosteric binding site with impact on the reaction kinetics, which may explain some of the kinetic complexity (10,22,24,28) and cooperativity reported for this enzyme (15).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The remote folate binding site found here might represent crystallographic trapping (of no functional implications). Alternatively, it could indicate an allosteric binding site with impact on the reaction kinetics, which may explain some of the kinetic complexity (10,22,24,28) and cooperativity reported for this enzyme (15).…”
Section: Resultsmentioning
confidence: 98%
“…Furthermore, multiple studies have identified key differences in the molecular mechanism of catalysis between FDTSs and classic TSases (2,4,(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). These differences, along with the fact that the thyX gene is present in many human pathogens (e.g., bacteria causing Anthrax, Tuberculosis, Typhus, and other diseases), renders these flavo-enzymes as potential targets for rational inhibitor design, possibly affording compounds that might be effective antimicrobial drugs (11,(22)(23)(24).…”
mentioning
confidence: 99%
“…Inhibitors with high specificity for FDTS over TSase are sought, especially in low nanomolar K i range, which is something that may be aided by the fact that FDTS is the only known uracil-methylating enzyme without a catalytic nucleophile [28,43]. Substrate analogues have been examined for this endeavor, and crystal structures of Tm FDTS with a variety of possible inhibitors have been obtained.…”
Section: Inhibitor Designmentioning
confidence: 99%
“…Another avenue of inhibitor design for specificity of FDTS over TSase will take advantage of active site accessibility, where TSase has a much more cumbersome, deeply buried active site compared to FDTS [28]. This route would allow more chemical space to be explored for FDTS inhibitors due to the availability of space, as large inhibitors would face a steric barrier eliminating them from binding to TSase [28].…”
Section: Inhibitor Designmentioning
confidence: 99%
See 1 more Smart Citation